Sharia Compliance of Subsidized Mortgage Financing Products at Bank Jabar Syariah Garut - Lazuardi Arip Muhammad; Yudi Wahyudin; Ahmad Syaeful Rahman (Lembaga Publikasi Ilmiah Nusantara, 2026)
Subsidized mortgage financing is a government-supported housing program designed to help low- and middle-income families obtain affordable home ownership through Islamic banking institutions. At Bank Jabar Syariah Garut Branch, this financing scheme is implemented using the musyarakah mutanaqishah contract, under which the ownership certificate is registered in the customer’s name from the beginning of the financing period. This practice raises legal questions regarding its compliance with the principles of Islamic Economic Law and the applicable DSN-MUI fatwas. Therefore, this study aims to analyze the implementation of subsidized mortgage financing based on the musyarakah mutanaqishah contract and examine the legal status of registering the financed property under the customer’s name. The study employs an empirical juridical approach with a qualitative research design. Data were collected through interviews, observations, and documentation, and analyzed by comparing banking practices with the provisions of Islamic Economic Law and relevant DSN-MUI fatwas. The findings show that the implementation of subsidized mortgage financing at Bank Jabar Syariah generally complies with sharia principles and is consistent with DSN-MUI Fatwa No. 73/DSN-MUI/XI/2008 concerning Musyarakah Mutanaqishah. Furthermore, the registration of ownership certificates under the customer’s name is permissible under DSN-MUI Fatwa No. 01/DSN-MUI/X/2013, provided that it is based on mutual agreement and the agreed ujrah mechanism. These findings provide empirical evidence that the financing model implemented by Bank Jabar Syariah is legally and sharia compliant while offering practical guidance for the implementation of Islamic home financing products in Indonesia.